Education in the View of Realism Philosophy - Saputri, Helen (Yayasan Sembilan Pemuda Indonesia, 2024)
This article delves into the essence of the philosophy of realism and its relationship to education, exploring how the principles of realism can shape more meaningful learning experiences. The main focus is on the application of realist concepts in educational contexts, how educators and educational leaders can incorporate these principles to create relevant and rewarding learning environments. The article first discusses the basic principles of the philosophy of realism, underscoring the view that objective reality is accessible through rational observation and analysis. Next, the article explains how the philosophy of realism can provide a solid foundation for establishing pragmatic educational goals, preparing individuals to face the real world with deep understanding. In the context of education, the article highlights the role of teachers as learning facilitators who guide students to understand reality and develop critical thinking skills. Discussions on practical experience and direct observation as effective learning methods are also emphasized, as well as the need to integrate ethical values in the educational process. The application of the philosophy of realism in education is illustrated through some concrete examples in education. The article illustrates how a curriculum that is relevant to real needs, character development, and an emphasis on lifelong experiences are part of the education process.